Perceived Sensory Characteristics of Blended and Ambiguous "Concept" Flavors Among Adolescent and Young Adult E-cigarette Users. Issue 3 (27th January 2023) - Kreslake, Jennifer M; O'Connor, Katie M; Stephens, Daniel; Vallone, Donna M; Hair, Elizabeth C
Abstract: Introduction: Flavors with names describing blended tastes/sensations or with ambiguous terminology ("concept flavors") are available on the e-cigarette market. Aims and Methods: This study investigates adolescent and young adult use and sensory perceptions of blended and concept flavors. Current e-cigarette users aged 15–24 years ( N = 2281) completed an online convenience sample survey (October 20–November 23, 2020) and rated the sensory attributes (fruity, cooling, sweet, and minty) of their current flavor(s) using nine-point scales. T -tests compared mean sensory perception scores within and between flavors. To compare concept flavors to blends, reference categories used the average of blends with relevant descriptors: fruit (Banana Ice, Iced Mango, Melon Ice, Cool Cucumber); cooling (Banana Ice, Iced Mango, Melon Ice, Blue B Ice, Cool Cucumber, Lush Ice, and Menthol Purple); sweet (Vivid Vanilla) and mint (Mint-sation). Results: Most respondents had used at least one product with blended descriptors (74.8%) or concept flavor (57.9%) in the past 30 days. All flavors had high perceived strength for at least two sensory attributes. Mint taste was not perceived to be a strong sensory characteristic for all but two flavors (Mint-sation and Winter) in the study. The most commonly used flavors used blended descriptors (Iced Mango was used by 30.2% of the sample; Banana Ice: 26.2%; Lush Ice: 23.8%; Melon Ice: 22.9%). Some concept flavors did not significantly differ from flavor blend reference categories for strength of: fruit taste (Bahama Mama and Tropic); cooling sensation (Marigold, Island Breeze, Winter); sweet taste (Bahama Mama, Honeymoon, Island Breeze, Island Cream, Meteor Milk, OMG, Royal Dagger and Tropic); and mint taste (Winter). Conclusions: Blended and concept flavors are used by most young e-cigarette users, who describe these products as fruity, sweet, and cooling. A variety of flavored products with high youth appeal are available in the U.S. market. Implications: This study of adolescent and young adult e-cigarette users finds evidence of the popularity of e-cigarette flavors combining a cooling sensation with fruity and sweet flavorings. Some products with this flavor profile do not use characterizing descriptors. Findings inform public health interventions intended to reduce e-cigarette use in young people.